Evidence of different phylogenetic origins of two mexican sugarcane mosaic virus (scmv) isolates (2012)
The molecular analysis of the Sugarcane mosaic virus (SCMV) for coat protein cistron reported in the public GenBank database, revealed the presence of 45 additional nucleotides coding for 15 amino acids in the N-terminal region of the coat protein sequence of the mexican isolate GU474635. BLAST analysis indicates this particular feature is also present in the coat protein sequence identified with the accession number D00949 reported in the USA in 1991. Phylogenetic analysis of 185 SCMV coat protein sequences reported from Asia, Africa, Brazil and Argentina among others, suggest a putative different phylogeographical origin of the mexican SCMV isolates. Coat protein sequence from isolate GU474635 is phylogenetically closer to isolates from Brazil and USA, while SCMV coat protein sequences from Germany and Spain are phylogenetically closer to the coat protein from isolate EU091075. Particular features among SCMV isolates from different countries along the American continent, i.e USA, Mexico and Brazil suggest low phytosanitary control in plant material exchange among countries.